2018
DOI: 10.3906/kim-1706-51
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of new oxindoles as analogs of natural product 3,3′-bis(indolyl)oxindole and in vitro evaluation of the enzyme activity of G6PD and 6PGD

Abstract: Natural and synthetic derivatives that contain an indole core are being used in medical treatments and technological processes. Therefore, the development of new synthetic methods for the synthesis of indole derivatives is very popular. In this study, new oxindoles with reaction of 4,7-dihydro-1 H -indole (2) and isatin (4) were synthesized as analogs of natural product 3,3 ′ -bis(indolyl)oxindole. The biological properties of the compounds obtained during this study were also studied, showing that compounds 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 15 publications
2
25
0
1
Order By: Relevance
“…[13,[21][22][23][24] To date, only a few G6PD inhibitors have been available with high IC 50 values, which negatively affect their use as therapeutics and basic research probes. [13,[21][22][23][24] To date, only a few G6PD inhibitors have been available with high IC 50 values, which negatively affect their use as therapeutics and basic research probes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[13,[21][22][23][24] To date, only a few G6PD inhibitors have been available with high IC 50 values, which negatively affect their use as therapeutics and basic research probes. [13,[21][22][23][24] To date, only a few G6PD inhibitors have been available with high IC 50 values, which negatively affect their use as therapeutics and basic research probes.…”
Section: Discussionmentioning
confidence: 99%
“…[13,38,39] It is of interest that these groups have free electrons and suitable geometries that can easily interact with the active site amino acids in the structure of the enzymes. In our work, the results demonstrated that the derivatives containing N-substituted indolines had no effect on the activity of G6PD and 6PGD whereas the compounds with N-benzoylindoles inhibited the enzymatic activ- In the current research, it has been determined that organic molecules containing sulfur, nitrogen, oxygen, and halide groups in the structure of molecules are strong inhibitors of enzymes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[51] Çiftci et al [52] investigated effect of some plant hormones on rat erythrocyte G6PD enzyme activity. Bayındır et al [53] investigated in vitro effect of new oxindoles derivatives on rat erythrocyte G6PD and 6PGD enzymes activity. Another study deals with effect of ethanol on rat and human erythrocyte G6PD enzyme activity.…”
Section: F I G U R Ementioning
confidence: 99%